The Influence of Transformational Leadership, Service Motivation of Administrative Staff, School Organizational Climate on the Quality of Administrative Services at Padang City State Senior High Schools - Hastuti, Dwi Fuji; Irsyad, Irsyad; Rusdinal, Rusdinal; Damanik, Enceria (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2026)
This study aimed to develop and evaluate a structural model explaining the quality of administrative services through transformational leadership, service motivation, and school organizational climate in public senior high schools. A quantitative causal design was employed involving 90 teachers from three public senior high schools in Padang City. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that the proposed model demonstrates substantial explanatory power (R² = 0.707), adequate predictive relevance (Q² > 0), and good model fit (SRMR = 0.091), suggesting that transformational leadership, service motivation, and school organizational climate collectively provide a robust framework for explaining administrative service quality. The novelty of this study lies in integrating these three organizational factors into a single structural model to explain administrative service quality. Practically, the findings highlight the importance of strengthening leadership practices, enhancing service motivation, and fostering a supportive organizational climate to improve the quality of administrative services in schools.